On some benthic hydroids from New Zealand deep waters, with the description of a new species - Cantero, Álvaro Luis Peña (Zootaxa, 2023)
Six species, including Symplectoscyphus trabeculatus sp. nov., have been found and studied in a small collection of benthic hydroids from deep waters south of New Zealand’s South Island. All species belong to Leptothecata, in particular to the families Campanulariidae, Hebellidae, Lafoeidae, Sertularellidae, Symplectoscyphidae and Zygophylacidae, all of them represented by a single species. Half of the species represent new records for New Zealand waters and Hebella macroplana Watson, 2019 is found for the second time and its gonotheca, hitherto unknown, is described.